REDESAIN RUANG TERBUKA HIJAU TAMAN ALOK GALING DI KOTA SAMBAS - Riyanto Djoko; A. Sudrajat (Universitas Tribhuwana Tunggadewi, 2015)
Landscape can gives identity to a place, and hence diversity to the setting places of lives. Alok Galing Park as a Sambas’s area haven’t developed comprehensively yet. Considering proportion of functional and aesthetics aspects, which have ideal value in describing its development, hopped that Alok Galing Park become a harmony landscape as Sambas city’s indentity. The research goal is redesigning Alok Galing Park as city’s welcome area. The research was conducted by site-observation to collect data. Collected data consist of primary data include physical, biophysical, socio-cultural economic aespects, and secondary data that some relevant literatures. Data were analyzed descriptively. The results showed that redesigning Parks Alok Galing implemented by changing the land form which was originally seems like valleys into the hills. Ironwood (Eusideroxylon zwageri) is added as a city’s specific characteristic. Welcome Monument at the site will be retained in order to maintain the synergy between Saing Rambi Monument and Alok Galing Park. Several types of vegetation added like trees: Betel palm (Arace catechu), Auri (Acacia auriculiformis) and Japanese fern (Fellicium decipiens); shrubs: Skyflower (Duranta erecta) and Shoe flower (Hibiscus rosasinensis; groundcovers: Pinto nuts (Arachis pintoi) and Elephant grass (Pennisetum purpureum). Several site utilities such as plumbing installation, electrical and drainage network were added too